2020
DOI: 10.3389/fphys.2020.00631
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression Profiling of Three Transformer-2 Splice Isoforms in the Redclaw Crayfish, Cherax quadricarinatus

Abstract: Sex determination/sex differentiation is determined by genetics, environmental factors, or the interactions of the two. The Transformer-2 (Tra-2) gene plays an important role in the sex determination cascade signal pathway in insects. In this study, the Tra-2 gene was isolated and characterized from the cDNA library of gonad tissues in the redclaw crayfish, Cherax quadricarinatus. Three splice variants were identified, designated as CqTra-2A, CqTra-2B, and CqTra-2C, and sequence analysis showed that they had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…And, the silencing of Bttra2 or Btdsx resulted in male genital deformities (Guo et al, 2018). We were also found that Cqdsx was significantly reduced in the RNAi of CqTra2 in redclaw crayfish (Cai et al, 2020). These results indicate that Hcdmrt is also regulated by Hctra-2, but the regulation is different between the sexes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…And, the silencing of Bttra2 or Btdsx resulted in male genital deformities (Guo et al, 2018). We were also found that Cqdsx was significantly reduced in the RNAi of CqTra2 in redclaw crayfish (Cai et al, 2020). These results indicate that Hcdmrt is also regulated by Hctra-2, but the regulation is different between the sexes.…”
Section: Discussionmentioning
confidence: 66%
“…In medaka (Oryzias latipes), tra-2 transcripts (tra-2a and tra-2b) were mainly expressed in hermaphroditic germ cells before and during their sex differentiation, indicating that both tra2a and tra2b may be involved in the sex differentiation (Shiraishi et al, 2004). Cqtra-2 may play a role in sexual differentiation in the redclaw crayfish (Cherax quadricarinatus), which is mainly expressed in the ovary and gradually increases with embryonic development (Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…nipponense [ 43 ], and C . quadricarinatus [ 44 ]. Although the nucleotide sequences are similar to D .…”
Section: Discussionmentioning
confidence: 99%
“…This study identified and characterized putative sex determining genes in P. monodon , including PmOvtra 2 , Pmfru-1 , and Pmfru-2. Transformer 2 has been reported as a key gene for sex determination in some insects and crustaceans by regulating RNA splicing ( Cai et al, 2020 ). Transformer 2 protein forms a heterodimer with Tra protein and acts as a splicing factor on downstream RNA that requires sex-specific splicing ( Nöthiger & Steinmann-Zwicky, 1985 ).…”
Section: Discussionmentioning
confidence: 99%